A resina de protium heptaphyllum e seu principal constituinte, a mistura de triterpenos alfa e beta-amirina, previnem a obesidade induzida por dieta em camundongos: evidências e potenciais mecanismos - Carvalho, Karine Maria Martins Bezerra (2015)
Obesity which is characterized by excessive accumulation of body fat mainly due to the increased consumption of high-calorie foods and sedentary lifestyle is associated with various pathological conditions such as cardiovascular disease, diabetes, musculoskeletal disorders and cancer. Pharmacologic options for the treatment of obesity are limited and have many side effects. In Brazil only two drugs are available, sibutramine and orlistat. In the search for new therapeutic options for the treatment of obesity, medicinal plants have been an important source of research, particularly the terpene compounds, known regulators of blood glucose and lipid metabolism. This study investigated the antiobesity effect of Protium heptaphyllum resin (RPH) and its main constituent, the mixture of triterpenes alpha and betaamyrin (AMY), in obesity induced by high calorie diet in mice and its possible mechanisms of action. Swiss albino male mice were used, weighing between 20-25g, which after a week of free access to standard chow (Purina®, Brazil) were divided into 7 groups of 10 animals each and treated with standard diet (SD), high-fat diet (HFD), HFD+RPH 10mg/kg, HFD+RPH 20mg/kg, HFD+AMY 10mg/kg, HFD+AMY 20 mg/kg or HFD+sibutramine 10mg/kg (SIB) for 15 weeks. RPH and AMY were initially diluted in 2% Tween 80 in water. The HFD group received the same vehicle. SIB was diluted with water. Vehicle, RPH, AMY and SIB were replaced twice a week. The evaluation of obesity parameters consisted of measurements of body weight, abdominal adipose tissue and liver, as well as determination of glucose, amylase, lipase, ALT, AST, total cholesterol, triglycerides, insulin, ghrelin, leptin, TNF- , MCP-1, IL-6 and plasma resistin, triglycerides and cholesterol, and histological evaluation of liver and abdominal fat. It was also evaluated the gene expression of PPARy and lipoprotein lipase (LPL) in abdominal adipose tissue and the effect of PHR on adipogenesis in vitro. The animals that received only the high-fat diet (HFD), at the end of the 15th week, showed significant increase in body weight, liver and abdominal fat and plasma levels of glucose, amylase, lipase, ALT, AST, total cholesterol and triglycerides when compared to group that received the standard diet (SD). The animals treated with RPH 10 and 20mg/kg, AMY 10 and 20mg/kg and SIB 10 mg/kg showed a significant reduction of body weight, liver and visceral fat and plasma levels of glucose, amylase, lipase, ALT, AST, total cholesterol and triglycerides in relation to the HFD group. Only RPH 10 mg/kg did not significantly alter plasma levels of lipase compared to the HFD group. HFD increased significantly total cholesterol and hepatic triglycerides in comparison to HFD and this increase was significantly reduced by RPH, AMY and SIB. Feed intake was significantly higher in animals that received HFD compared to animals of SD, and this consumption was significantly reduced by RPH, AMY and SIB. There was no significant difference between the groups regarding water consumption. In addition, treatment with RPH 10 and 20 mg/kg, AMY 10 and 20 mg/kg and SIB 10 mg/kg reduced plasma leptin and insulin levels compared to animals that received only HFD. Plasma levels of ghrelin appeared in the HFD significantly reduced when compared to SD, while RPH increased significantly ghrelin levels in relation to HFD, these were reduced by AMY and SIB. Only RPH 20 mg/kg and AMY 20 mg/kg reduced significantly plasma resistin levels in relation to HFD. HFD significantly elevated plasma levels of TNF- , IL-6 and MCP-1 compared to the SD. RPH, AMY and SIB significantly reduced IL-6 and MCP-1 levels, while for TNF- it was observed a reduction with RPH 20mg/kg and AMY 10 and 20mg/kg. There was a significant increase of PPAR mRNA and LPL expression in adipose tissue of the HFD group compared to SD. RPH and AMY caused significant reduction of PPAR and LPL expression, but the same was not observed with SIB. The adipocytes area was significantly bigger in HFD animals compared to SD animals and it was reduced by RPH, AMY and SIB. While HFD promoted a liver inflammation with necrosis and steatosis signs, this was prevented by RPH 20 mg/kg, AMY 20 mg/kg and SIB. RPH 12.5; 25 and 50 μg/mL significantly reduced adipogenesis in vitro, observed by the reduction of the accumulation of lipids in 3T3-L1 cells and by down-regulation of protein expression of PPAR , C/EBP and C/EBP- . These findings suggest RPH and AMY have a preventive anti-obesity potential for their modulatory effects on carbohydrates and lipids metabolism, on the regulation of hormones regulating hunger and satiety on adipokines and cytokines in addition to the regulation of adipogenesis.